A convergent parallel mixed methods study of the end-of-life care experiences of people with intellectual disability in Ireland: Lessons learned from IDS TILDA. - Ryan, Karen Rebecca (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2023)
Palliative care is a vital intervention to relieve the suffering of people living with, and dying from, life-limiting conditions. However, people with an intellectual disability experience inequity in their access to, and experience of, palliative care. Progress in addressing care deficits has been slowed by the fact that the evidence-base is largely limited to small scale, descriptive studies. The Intellectual Disability Supplement to the Irish Longitudinal Study on Ageing (IDS-TILDA) is a longitudinal study studying the circumstances of adults with an intellectual disability aged 40 years or older who are resident in Ireland. It offers opportunity to study palliative care experience in a rigorous manner. The IDS-TILDA End-of-Life Care study is a convergent parallel mixed methods study situated within IDS-TILDA whose purpose is to understand the end-of-life care experiences and service utilisation of people with an intellectual disability in Ireland from the perspective of bereaved caregivers. Data is collected using survey and interview methods. Findings demonstrate that decedents were reported by carers as experiencing need in physical, emotional, psychosocial, spiritual, communication, decision-making, continuity of care and disability-related domains. They emphasised the importance of including family, intellectual disability staff and peers within the 'unit' of palliative care provision. A conceptual model of the Intellectual Disability Palliative Care Ecosystem was developed and tested and provided comprehensive insight into factors influencing need and complexity. Strengths in palliative care provision were observed; 43.6% of the population accessed specialist palliative care, quality of care was rated highly and 50.7% died in their usual place of care. Areas of deficit warranting attention were observed; they included addressing communication, spirituality, support for peers and staff. The study provides a comprehensive understanding of the range of factors influencing whether people with an intellectual disability 'live well' with a life-limiting condition and experience a 'good death'. Future waves of IDS-TILDA offer opportunity to understand which combinations of services and support are most strongly associated with cost-effectiveness and benefit.
APPROVED
Keywords: intellectual disability; learning disability; palliative care; longitudinal study; aging; end of life care